THE EFFECTIVENESS OF USING AUDIO VISUAL MEDIA ON STUDENTS WRITING ABILITY IN DESCRIPTIVE TEXT - Henny Yulia; Heni Fitri Mahesa; Merie Agustiani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2023)
The objectives of this research was to know the effectiveness of using audio visual media on students writing ability in descriptive text to eighth grade at SMP Negeri 1 Runjung Agung. The type of study was quasi-experimental. There were two classes namely VIII.1 as experimental group the total number students 27 and VIII.2 as control group the total number students 27. The sample was choosen by using purposive sampling. The result of students’ pre- test in experiment class showed that the minimun score was 22.50 and maximun score was 72.50, and then mean score was 56,57. The result of students’ pre-test control class showed that the minimum score score was 20.00 and maximum score was 92.50, and then mean score was 52.96. The result of students’ post-test in experiment class showed that the minimum score was 65.50 and maximum score was 95.00, and then mean score 84.44. The result of student’ post-test in control class showed that the minimum score 52.50 and maximum score was 72.50, and then mean score was 64.44. The result of t-test found the calculated value of t-obtained was 10.766, in two tailed testing with df =26, the critical of t-table was 2.045. Since the value of t-obained was higher than the critical value of t-table, it means that there was a significant difference in achievement before and after the treatment. Therefore t-obtained was higher than t-table. This indicated that Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. It means that there is the effectiveness of using audio visual media on students writing ability in descriptive text to eighth grade at SMP Negeri 1 Runjung Agung.